Social capital and oral health promotion: Past, present, and future challenges - Knorst, Jessica Klöckner; Vettore, Mario Vianna; Ardenghi, Thiago Machado (Frontiers in Oral Health, 2022)
Social capital has been widely inserted in health discussions in recent decades. In this sense, social capital has become a popular term and has been highlighted as one of the main determinants of health in the conceptual framework of the social determinants of the World Health Organization. The concept of social capital focuses on the positive consequences of sociability and places these consequences in the broader discussion of capital. In this sense, social capital reflects the benefits that individuals and communities derive from having broad social networks or high levels of social trust. Despite controversies regarding its definition and numerous criticisms, a growing body of evidence suggests that high levels of social capital benefit oral health. This factor has also been recognized as a potential softener of the impact of oral conditions on oral health, through behavioural and psychosocial processes. Thus, efforts to reduce inequities in oral health preferably should be based on their origins and on their complex causal process, such as the social determinants. The future challenges in the area are specially related to the development of interventions and health promotion actions that aim to stimulate social capital, aiming to reduce the impact of social inequalities on oral health throughout the life course.